AT THE MERCY OF THE FLESH: THE INCARNATION AND HISTORICAL CONTEMPLATION. - Kugler, Michael (Fides et historia, 2015)
The author reflects on how the Incarnation of Jesus Christ can help Christian historians and Christians generally think differently and sensibly about the past. He explains his definition of Incarnation and the main historical implications of trust in God who reveals Himself by taking on human flesh. He also speculates on the pressure an incarnational conviction might create for the lives of Christian historians.